ستخالص الهالم النباتي من بذور الكتان .L usitatissimum Linum المزروع في العراق - شاكر خالدة عبد الرحمن; العبادي إيناس مظفر; الجبوري أحمد حسين (Al-Nahrain Journal of Science, 2018)
Chemical composition of flaxseed was estimated including moisture, ash, protein, fat and carbohydrates. They were 5.07, 3.80, 25.66, 40.20 and 25.27%, respectively. Extraction was carried out under different conditions of temperature, time, pH and mixing ratios of seeds: water. The choice fell on three transactions which gave the highest yeild of the mucilage. The highest yeild of mucilage was obtained when flaxseed were extracted with boiling water. It showed darker color than the mucilage extracted by the chemical method. An increase in the yeild of the mucilage extracted from flax seeds was observed with increased in size compared to ethanol precipitation. Results showed that the temperature is one of the most influential factors in the yeild of the mucilage affecting the ratio of water to seeds under lower pH values. Results concluded preferential removal of fat from flaxseeds to obtain a high yield of mucilage compared with intact seed. The Chemical composition of three mucilage estimated rates at moisture, ash, protein, fat and carbohydrates. The total percentages were 9.5, 13.5, 10.29, 0.36, 66.3% for the first and 9.4, 12.8, 14, 0.34, 63.4% for the second and 7.8, 6.2, 7.18, 0.46, 78.3% for the third respectively.